The Influence of Consumer Behavior and Ease of Transactions on the Use of E-Money (Case Study of Transjakarta, Tanjung Priok Sub-District) - Siti Mariam; Kartika Sari; Fachmi Tamzil (President University, 2023)
This study aims to analyze the effect of consumer behavior and ease of transaction on the use of e-money (Case Study of Transjakarta in Tanjung Priok District) partially and simultaneously. This research uses quantitative research. The analysis technique used multiple linear regression analysis. Data analysis used IBM SPSS Statistics Version 26 Program. The research population was 800 respondents using E-money consumers. The results of the study: (1) There is a positive and significant influence of consumer behavior on the use of e-money, with the magnitude of the effect of 32.6%. (2) There is a positive and significant effect of Ease of Transactions on the Use of E-money, with a magnitude of 24.3%. (3) There is a positive and significant effect of Consumer Behavior and Ease of Transactions on the Use of E-money, with a magnitude of 36.1%.